PERKEMBANGAN KOGNITIF ANTARA HUBUNGAN BAHASA DAN PROSES BERPIKIR DALAM BERKOMUNIKASI DI MEDIA SOSIAL - Wildan Alvin Salis; Irwan Siagian (STKIP Subang, 2023)
This research examines the relationship between language proficiency and thought processes in the context of cognitive development. The aim of this study is to understand how language proficiency relates to thought processes, particularly in terms of the influence of language on the quality and effectiveness of one's thinking. The research method employed is descriptive qualitative analysis of literature. The results of the study indicate a significant relationship between language proficiency and thought processes. Good language proficiency, including a strong understanding of language, fluent speaking skills, and effective listening skills, is associated with better thinking abilities. Strong language proficiency has also been shown to influence the quality of one's thinking, including problem-solving skills, logical reasoning, and creative thinking.